Social Piety Index: A Measurement Strategy for The Manifestation of Individual Piety in Community Life to Support Regional - Sabri, Fadillah; Yusmaliana, Desfa; Vebrian, Rajab; Wantini, Wantini; Tohir, Muhamad (Postgraduate Program Magister Pendidikan Agama Islam, 2024)
This study aimed to analyze the measurement of the individual piety index as a manifestation of social piety in supporting regional development programs. Improving the quality of humans to increase the social piety of the community has become one of the priorities in realizing the development of competitive and noble humans. The research method applied was the Creswell model of library research, which is qualitative. Data was gathered from literature on social piety, regional development, and the social piety index. The data-gathering method followed the Sugiyono concept, which entailed a manual and digital search of relevant literature. The Moleong model was used in the data analysis technique. For this reason, several strategies that can be formulated to achieve these goals are outlined in the form of 1) increasing concern for others (social care); 2) increasing public awareness of environmental conservation; 3) increasing the community's awareness of the law, and 4) increasing public awareness of the values of pluralism (diversity). Several parts of the regional apparatus involved in realizing the achievement of the social piety index are all line levels in the community.